Potential worlds : Planetary memories & eco-fictions - Garayeva-Maleki, Suad.; Bratton, Benjamin; Bürge, Milena; Demos, T.J.; Fech, Anna; Garayeva-Maleki, Suad; Kaczor, Rabea; Negarestani, Reza; Parikka, Jussi; Munder, Heike (Zürich : Scheidegger und Spiess, 2020)
The ecological crisis the world is currently experiencing calls for an urgent rethinking of our relationship to nature, natural resources, and the entirety of life on Earth, as well as that of humans to each other. The time has come for repurposing coexistence, aided by post-human thought and technological advancement, and for realizing that humans are merely part of, rather than the center of, our world.00'Potential Worlds: Planetary Memories and Eco-Fictions', published in conjunction with group shows at Zurich?s Migros Museum für Gegenwartskunst and Baku?s YARAT Contemporary Art Space, questions forms of knowledge developed in the course of annexation of the environment and asks what ideas of nature might emerge from the current crisis and how we might perceive nature in the future. Thirty-six artists from around the world featured in this book examine the ecological and social consequences of the past and ongoing conquests of land for purposes of accumulating power and resources. Essays by Benjamin H. Bratton, T. J. Demos, Reza Negarestani, and Jussi Parikka shed light on multiple different perspectives, such as colonialism, post-humanism, ecology, and artistic adaption of new technologies, and investigate the potential future of mankind living in alliance with nature and the role of art in this undertaking as a technological, scientific, and social experiment. Concise texts on the work of the participating artists and an introduction by curators Suad Garayeva-Maleki and Heike Munder round out this illustrated volume.00Exhibition: Migros Museum für Gegenwartskunst, Zurich, Switzerland (07.03. - 11.10.2020).
Arunanondchai, Korakrit ; Benera, Anca ; Estefan, Arnold ; Budor, Dora ; Burton Nitta ; Fei, Cao ; Charrière, Julian ; Cheng, Carl ; Durham, Jimmie ; Fend, Peter ; Greenfort, Tue ; Hadjithomas, Joana ; Joreige, Khalil ; Mayer Harrison, Helen ; Harrison, Newton ; Henderson, Louis ; Maggic, Mary ; Mileece* ; Kyungwon, Moon ; Joonho, Jeon ; Villar Rojas, Adrian ; Yoldas, Pinar ; Bo, Zheng
Imported from: zcat.oclc.org:210/OLUCWorldCat (Do not remove)
boek